Playing the tape again-recovery for vochisia ferriginea a tree from Nicaraguan rain forest: A matrix trasition model / Javier Enrique Ruiz Pérez - Ruiz Pérez, Javier Enrique (Estados Unidos de Norteamerica, Wageningen University, 2000)
In 1988, the h~icane Joa_n caused severe struggles to the rain forest of the Nicaraguan Atlantic st. After this na11:1ral ~1stur~ance the species Vochysia (erruginea, experienced an exceptional em o~ regeneration m which almost all its individuals died with the storm and then its meranon was by thc w~y of advancc regeneration of its seedlings, until reaching its ndance as before the hurricane. vadays, the species has well regenerated in the hurricane forest ofNicaragua mainly by its fast wth, taking advances of plenty light conditions after the hurricane disturbance. This fast wth has been reduced advanced the process of regeneration but even so its growth formance is still faster than most of the species in the forest. rerruginea belongs to a well-studied group of fast growing species, its wood which is not of first quality has a fast growth that make it ideal for obtain revenue in forestry enterprises. lts, d can be used for insider carpentry, plywood, and others. Also has been reported that the cies could be planted, even as seedlings in degraded land, harvesting its wood in time periods W-40 years. At the same time that the plantation is growing is also possible to take care for the wth of accompanist regeneration of species of primary forest, reclaiming in this way rain est diversity; which has been reported to be very good below.f ferruginea understory. this economically potential species a clear understanding of its regeneration in such disturbed est is necessary to know actual and future population abundance in a way that perrnits arrive to ilogical and silvicultural management oriented objectives. order to get more insight about the species, its population behaviour and structure were studied i simulated, by the way of the application of standards matrix models analysis using height as mt variable. This analysis was compared with the results of the height-diameter matrix model: essed by Boucher & Mallona (1997). Those comparisons indicate that the species is near to a ble population growth after ~ hurricane, fire and drought occurrence. iapter 1 of this report present a background about regenerating process of. f ferruginea after: hurricane in Nicaragua. Scientific and practica] objectives and research are formulated: search question in chapters one are the answered on Chapter 8, which is the conclusion apter. Chapter 2 presents a brief taxonomy description of the species, ecological and onomical importance of V _ (erruginea is discussed under a regenerating secondary species Lmework, and a exceptional regenerating patter of the species after the big disturbance caused hurricane Joan in Nicaragua is discussed. Chapter 3 is an overview to current literature on odelling process. A pictorial model of. f _ferruginous was constructed and is discussed on the. sis of literature framework of the species. Chapter 4 present principles of tree height elopement that support the use of height as an input variable in a matrix model, aim of the atrix model are discussed on the base of those height development principies. Chapter 5 present e methodology to construct a matrix model focused on.f ferruginea.hapter 6 present results of the height-based model, which were calculated simultaneously for the une forest by the way of two matrices ( with and without fire occurrence ), sin ce the oc curren ce .fire in site with more abundance for the species was reported. The population Standard Stable Distribution was calculate as x.= 1.1057 far year without fire occurrence and '). = 1.0427 far year with fue occurrence. Indicating that the fue and associate drought does not conduct the forest to unstable situation but promote a pulse-stabilised climax by nearing '). to the hypothetical value of 1. Also projection of five height-stages in which the species was divided shows in just four periods of simulation there will be a number of 178 adult trees (higher than 1 O meter) per 0.93 ha in the period with fire occurrence. And a number of 173 adult individuals in the forest exposed fire occurrence. Such amount of trees may need silvicultura! management in near future. Also from chapter results, the elasticity analysis showed the importance of the adult trees as the stage that may conduct to an unstable situation to the species if a disturbance to this height stage occur or is carry out (fue, hurricane occurrence, intensive logging or unplanned thinning). Attempts to classify the species under the Grime model was conducted. Elasticity analysis was done sumrning the elasticity coefficient of the three regions of the population matrices: Growth (G) Stay (S) and Net-fecundity (F). Elasticity coefficient were plotted in a triangular graph, for both fue and not-fire occurrence in the forest. Those triangular graphs show the species as a Ruderal strategist preferring advanced regenerating forest, something that has to be taken as just an attempt of classification, because to the small sample size used and the lower demographic variation in the sample. Chapter 7 presents a discussion of the results of the matrix model. Discussion focus tum around the importance of Hurricane and small disturbance like fire ar drought occurrence in the actual and future abundance of the species. All analysis in chapter results has a correspondent headline in chapter 7 of discussion, which make easy to the reader to come back to the result frorr discussion or the other way around. Chapter 8 presents the conclusion by the way to answering research questions formulated iJ chapter 1. Chapter 9 corresponding to recomrnendations pointed out that results of this researcl might focus the interest of ONG and timber companies. In ali cases, well-developed and field tested silvicultural methods have to be used as a way to understand tbe population dynamic through ali the moment of management of the species.
Keywords: 1. PLANTS DEVELPMENT 2. REGENERATION (BOTÁNICA) 3. RECOVERY-VOCHYSIA FERRUGINEA 4. RAIN FOREST-NICARAGUA 5. THESIS-AGROFORESTRY RESEARCH